2021
DOI: 10.1302/2633-1462.27.bjo-2021-0027.r1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors influencing fracture characteristics in postoperative periprosthetic femoral fractures around cemented stems in total hip arthroplasty

Abstract: Aims This study evaluates risk factors influencing fracture characteristics for postoperative periprosthetic femoral fractures (PFFs) around cemented stems in total hip arthroplasty. Methods Data were collected for PFF patients admitted to eight UK centres between 25 May 2006 and 1 March 2020. Radiographs were assessed for Unified Classification System (UCS) grade and AO/OTA type. Statistical comparisons investigated relationships by age, gender, and stem fixation philosophy (polished taper-slip (PTS) vs compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Acetabular fracture is the largest weight-bearing injury of the articular surface of the whole body, and its treatment principle is the same as other intra-articular fractures, which requires anatomical reduction, firm fixation, and early joint function exercise [ 13 ]. In the past 30 years, active early open reduction and internal fixation for displaced acetabular fractures have been recognized by most scholars [ 14 ]. Although it can effectively reconstruct the anatomical structure of the acetabulum and restore its function, there are still some postoperative complications that affect the long-term efficacy due to many factors affecting the therapeutic effect, even if it is treated by experienced specialists [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acetabular fracture is the largest weight-bearing injury of the articular surface of the whole body, and its treatment principle is the same as other intra-articular fractures, which requires anatomical reduction, firm fixation, and early joint function exercise [ 13 ]. In the past 30 years, active early open reduction and internal fixation for displaced acetabular fractures have been recognized by most scholars [ 14 ]. Although it can effectively reconstruct the anatomical structure of the acetabulum and restore its function, there are still some postoperative complications that affect the long-term efficacy due to many factors affecting the therapeutic effect, even if it is treated by experienced specialists [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spina et al 18 reported a higher incidence of fractures in uncemented THAs when compared to cemented THAs across 28 years of postoperative follow-up, with a two-fold increase in the incidence of fractures for uncemented THAs within the first year. In contrast, the observational study by Jain et al 22 reported that 85.1% of the PPFs in their series occurred around cemented polished taper stems. Other series have reported that fractures around uncemented implants mainly occur intraoperatively, 30 and Miettinen et al 23 suggested that cementless fixation was an independent risk factor for PPF.…”
Section: Discussionmentioning
confidence: 78%
“…20 We also observed a variation in sex distribution dependent upon fracture type which was similar to other studies. 21,22 The NJR reports that 60% (total hip arthroplasty (THA)) and 56% (total knee arthroplasty) of primary arthroplasties are performed in females. This contrasts with a female proportion of 58% and 84% for hip and knee femoral PPFs, respectively, suggesting that sex is variably associated with the risk of a femoral PPFs dependent upon the joint involved.…”
Section: Discussionmentioning
confidence: 99%
“…Other series reporting on specific subsets of hip PPFs have reported higher operative rates of 84% to 94%. 9,10 In their analysis, Bottle et al 2 reported that both males and females over the age of 84 years were less likely to undergo surgery in comparison to younger patients, as well as those with increasing socioeconomic deprivation, chronic obstructive pulmonary disease, or a pre-existing neurological disorder. COMPOSE observed similar rates on nonoperative treatment in patients with comorbidities compared to those without comorbidities.…”
Section: Discussionmentioning
confidence: 99%